The Face of Orientalism: The western appropriation and commodification of Asian culture - Atmadja, Aaren Abigail (The Motley Undergraduate Journal, 2023)
Contemporary society today is made up of the intricate fusion of cultural systems. Bound by diaspora, culture becomes a site of open dialogue, wherein its legitimacy is contextualized and positioned by geographical location and traditional accuracy. The construction of cultural identities reflects the cultural norms and codes from which its characterization originates. This is the case for a Tik Tok commentary video made by Cantonese model and content creator Ka Laam Chan, where she presents a highly problematic representation of the Asian American identity and their experience. Despite being born and raised in Hong Kong for most of her life, Chan situates herself as the mouthpiece of all Asian persons in the Chinese diaspora. In situating Chan’s Tik Tok video as an emerging site of racial ontology where academic dialogue can take place, we can attempt to understand the nuanced delineation of the heterogeneity in the Chinese diaspora.